Not dead yet: cell death and survival in cancer and normal physiology - Green, Douglas R. (Frontiers in Cell Death, 2024)
For decades, we have assumed that all regulated cell death pathways have a dedicated “point of no return” that precedes death but after which cells are committed to die. The realization that this is often not the case represents what can be considered a paradigm shift in the field. Here we consider how cells can survive despite engagement of a cell death pathway and the consequences of a “near death experience” in cancer cells and possibly other physiological conditions.